Observational study on FNAC evaluation of peripheral lymph node swellings - Raj, Pulak; Kumar Choudhary, Pawan (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Peripheral lymphadenopathy is one of the common conditions encountered by clinicians. Knowledge of the pattern of diseases responsible for the same helps in better clinical decisions and management. The present study was conducted to assess the cytomorphological pattern of lymph node swellings by FNAC. Methods: The present study was cross-sectional in nature conducted upon 163 cases presenting with peripheral lymph node swellings for FNAC. Details of illness and findings of FNAC were noted. Results: Reactive hyperplasia was the most common finding in younger age groups (<20 years). Tuberculosis was more commonly seen in middle age groups (21-40 years). Malignant changes were more common in the elderly (>60 years). Conclusion: Reactive hyperplasia was the most common cause of lymphadenopathy in younger age groups was, tubercular lymphadenitis in the middle age group and metastatic carcinoma in patients above 60 years of age.